2019
DOI: 10.1250/ast.40.391
|View full text |Cite
|
Sign up to set email alerts
|

Identification of jet aircraft model based on frequency characteristics of noise by convolutional neural network

Abstract: We have been developing an aircraft model identification system that uses a convolutional neural network (CNN). The assumption is that this identification system would be used to estimate the number of flights to create noise maps. In our previous study, we used the CNN model to classify five aircraft comprising three rotorcraft, one turboprop, and one jet aircraft, and the accuracy reached 99%. In the present study, to examine whether this method is also effective for identifying the sound sources of jet airc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We have been developing an aircraft model identification system that uses field measurements and machine learning, the aim being to use the frequency characteristics of aircraft noise to automatically classify the aircraft model associated with aircraft noise events. In Morinaga et al (2019) [2], we summarized the results of our previous studies [3][4][5] and those of studies conducted in other countries [6][7][8][9][10][11][12][13]. We also reported the results of two case studies that were conducted in the vicinity of airports, each of which identified a different model of jet aircraft.…”
Section: Previous Studiesmentioning
confidence: 99%
“…We have been developing an aircraft model identification system that uses field measurements and machine learning, the aim being to use the frequency characteristics of aircraft noise to automatically classify the aircraft model associated with aircraft noise events. In Morinaga et al (2019) [2], we summarized the results of our previous studies [3][4][5] and those of studies conducted in other countries [6][7][8][9][10][11][12][13]. We also reported the results of two case studies that were conducted in the vicinity of airports, each of which identified a different model of jet aircraft.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The characteristic frequency distribution of these noise sources, especially the acoustically dominant sources, is used to develop acoustic noise [9] and noise immission models [10] that help predict the acoustic footprint of an aircraft. These unique acoustic signatures can also be used to identify specific aircraft [11,12]. The characteristic frequency distribution represents the superposition and linear and nonlinear interaction of all the acoustic modes.…”
Section: Contextmentioning
confidence: 99%
“…noise levels. However, when more complicated classification is required, such as distinguishing military aircraft other than fighter aircraft, it is necessary to deal with the aircraft model identification technique based on a continuous recording of frequency characteristics [8].…”
Section: Agenda Toward Aircraft Noise Mapping In Viet-mentioning
confidence: 99%